2023
DOI: 10.5354/0718-8358.2023.67828
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de beneficios y co-beneficios de las viviendas energéticamente eficientes. Un análisis para Barcelona

Abstract: El parque edificado europeo es responsable del 36% de las emisiones de gases de efecto invernadero y del 40% del consumo de energía y su rehabilitación reduciría un 26% del consumo. Además de los beneficios económicos de esta reducción, como su incidencia en reducir la pobreza energética, las viviendas energéticamente eficientes implican co-beneficios en el confort y la salud de sus habitantes; sin embargo, los hogares no son conscientes de ello, lo que, aunado a otras barreras, desincentiva la obtención de vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…However, it was limited to the winter period, relegating the fact that summer produces thermal stress aggravated by heatwaves in the Mediterranean area. Biere Arenas, R. et al [10] used a survey and identified that perceived financial benefits (e.g., energy savings) and co-benefits (e.g., comfort and health) of efficient homes are contingent on the socio-demographic characteristics of the population. Older and higher-income people appreciate more co-benefits, such as health, comfort, and environmental conservation, but younger and lower-income people value economic aspects more.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was limited to the winter period, relegating the fact that summer produces thermal stress aggravated by heatwaves in the Mediterranean area. Biere Arenas, R. et al [10] used a survey and identified that perceived financial benefits (e.g., energy savings) and co-benefits (e.g., comfort and health) of efficient homes are contingent on the socio-demographic characteristics of the population. Older and higher-income people appreciate more co-benefits, such as health, comfort, and environmental conservation, but younger and lower-income people value economic aspects more.…”
Section: Introductionmentioning
confidence: 99%
“…However, these valuations have been criticised by arguments referring to the "commodification of services" [16] or aspects involving the value of life in countries with different income levels. Few have employed a methodology in which co-benefits are studied at the level of people's perceptions [9][10][11], but none have studied them merely at the level of health co-benefits by focusing on perceptions of health and their impact on undertaking energy retrofits.…”
Section: Introductionmentioning
confidence: 99%
“…People tend to focus more on addressing climate change or reducing energy bills than acting out of an awareness of the impact on comfort and health [7][8][9][10]. The EnerValor1 project highlights that people are more willing to carry out improvements on their homes for functionality and aesthetic purposes than for energy efficiency reasons.…”
Section: Introductionmentioning
confidence: 99%